Pengaruh Sales Promotion Girl Smartphone Vivo Terhadap Minat Beli Konsumen di Kota Bima - Dita Aprilay Utami Putri; Muhajirin Muhajirin (Journal of Business and Economics Research (JBE), 2020)
This promotion is conducted to find out and analyze the partial Vivo Smartphone Sales Promotion of Consumer Purchase Interests in the City of Bima. in this research, the type of research used is associative. Probability Sampling technique is a sampling technique used. The number of samples used is 96 respondents using the probability sampling method. Based on the results of a partial analysis of this study shows that the Sales Promotion of Smartphone Girls Vivo (X) has a significant influence on Purchase Interest (Y) with a value (p value) 0.003 <0.05